The Application of Stress Modifiers as an Eco-Friendly Approach to Alleviate the Water Scarcity in Ajwain (Carum copticum L.) Plants - Saeid Heydarzadeh; Ahmad Tobeh; Sodabeh Jahanbakhsh; Salim Farzaneh; Ermenegilda Vitale; Carmen Arena (Plants)
Stress modifiers are recognized as biostimulants providing beneficial effects on various plant species. However, the specific potential of modulators such as melatonin, chitosan, humic acid, and selenium in enhancing the resistance of ajwain (Carum copticum L.) plants to water scarcity remains an open question. To address this knowledge gap, we conducted a randomized, field block-designed factorial experiment over two years (2022–2023) to compare the effectiveness of these biostimulants in mitigating the impact of water shortage on ajwain plants. This study involved three irrigation regimes: 100% field water capacity (FC100%—unstressed), 75% irrigation deficit (FC75%—moderate) and 50% irrigation deficit (FC50%—severe), and four modifier treatments (melatonin, chitosan, humic acid, selenium), plus untreated controls. Plant growth, seed yields, essential oil production, as well as eco-physiological traits were studied to assess the efficacy of these compounds as stress modulators. Water regimes and stress modifier applications, as a single factor or in synergy, significantly affected plant physiology and seed yield, highlighting the importance of sustainability in agricultural practices. Compared to FC100%, biological and seed yield, chlorophyll, and nutrient content decreased under FC75% and FC50%, while essential oil production, proline, soluble sugars, flavonoids, phenols and antioxidant enzymatic activity increased. Notably, regardless of the type of modulator used, the application of these modifiers improved all physiological attributes under moderate and severe irrigation deficits. Among the involved compounds, melatonin induced the most pronounced effects, leading to higher biological and seed yield, essential and fixed oil production, relative leaf water content, chlorophyll and nutrient concentration, and antioxidant activity. Our results demonstrate that such compounds effectively function as stress modulators against water scarcity in ajwain plants by preserving specific eco-physiological traits and promoting water saving. These findings provide valuable insights into their use as a nature-based solution for addressing water stress in sustainable agriculture and climate change challenges.